Utility of Nasal Debridement Following Pediatric Functional Endoscopic Sinus Surgery: A Scoping Review - Jeeho D. Kim; Bastien A. Valencia-Sanchez; Beau Hsia; Saif A. Alshaka; Gabriel Bitar; Vijay A. Patel (Sinusitis)
The role of second-look endoscopy and debridement (SLED) remains uncertain in children due to the perceived need for additional general anesthesia following their initial functional endoscopic sinus surgery (FESS) while mitigating risks and healthcare costs. This comprehensive review synthesizes current evidence on SLED in children, focusing on its practice pattern and treatment outcomes. This review was designed and performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews Protocol. Independent queries of the PubMed Central, MEDLINE, and Bookshelf databases were performed. A total of 53 relevant, unique articles were initially identified; 12 articles were ultimately deemed appropriate for inclusion in final analysis. The most common indication for FESS was chronic rhinosinusitis or recurrent sinus infections while that for SLED under general anesthesia varied from institutional practice patterns to surgeon preference. No meaningful comparison of outcomes was possible as the “success rates” of FESS with or without SLED were largely based on unvalidated questionnaires and equally subjective surgeon assessments. Even when looking at outcomes based on revision rates, FESS with SLED was considered successful between 60.5% and 95.6% of the time, with a mean of 84.2%, while FESS without SLED was successful between 71.0% to 96.4% of the time, with a mean of 86.3%. However, no randomized, controlled studies were available in the pediatric literature pertaining to FESS with or without SLED. Moreover, it became apparent that previous conclusions on the utility of SLED were based on the outcomes of FESS following one single SLED under general anesthesia vs. no SLED. As such, there is an unmet need to examine the utility of serial, office-based SLED in children to better elucidate its utility in pediatric FESS.